Measurement of Metabolites Associated with Nonaqueously Isolated Starch Granules from Immature Zea mays L. Endosperm - Liu, Ting-Ting Y. (1981)
Starch granules with associated metabolites were isolated from immature Zea mays L. endosperm by a nonaqueous procedure using glycerol and 3-chloro-1,2-propanediol. The soluble extract of the granule preparation contained varying amounts of neutral sugars, inorganic phosphate, hexose and triose phosphates, organic acids, adenosine and uridine nucleotides, sugar nucleotides, and amino acids. Based on the metabolites present and on information about translocators in chloroplast membranes, which function in transferring metabolites from the chloroplast stroma into the cytoplasm, it is suggested that sucrose is degraded in the cytoplasm, via glycolysis, to triose phosphates which cross the amyloplast membrane by means of a phosphate translocator. It is further postulated that hexose phosphates and sugars are produced from the triose phosphates in the amyloplast stroma by gluconeogenesis with starch being formed from glucose 1-phosphate via pyrophosphorylase and starch synthase enzymes. The glucose 1-phosphate to inorganic phosphate ratio in the granule preparation was such that starch synthesis by phosphorylase is highly unlikely in maize endosperm.